Immunosensors developed on clathrate platform compounds - Nohako, Kanyisa (University of the Western Cape, 2015)
Philosophiae Doctor - PhD === Organic noncyclic compounds were used in the development of immunosensor for rapid fish species detection. Flourene derivatives show unique chemical and physical properties because they contain a rigid planar biphenyl unit, and the facile substitution at C9 position of the flourene can improve the solubility and processability of materials containing flourene without significantly increasing of steric interactions in the compounds backbone. 9-(4- methoxyphenyl)-9H-xanthen-9-ol is bulky, rigid and has an hydroxyl moiety that may act as a hydrogen – bond donor, as well as a pyranyl oxygen which is a potential hydrogen –bond acceptor. We have successfully synthesised 9,9’-(ethyne1,2-diyl)bis(flouren-9-ol) by reflux method and 9-(4-methoxyphenyl)-9H-xanthen-9-ol through stirring at room temperature. The products were characterised using spectroscopic methods and were found to be both UV/Vis active (λmax = 400 nm flourene derivative and λmax = 337 nm xanthene derivative ) and fluorescent (440nm and 467nm flourene derivative and 344 and 380 xanthene derivative). These compounds were drop coated onto commercial glassy carbon electrode (GCE) to produce thin films. Scan rate dependent cyclic voltammetry (CV) confirmed the electrodynamics of the thin films to be consistent with monolayer diffusion (De = 1.37x10-21 cm2/s flourene derivative and De = 9.79x10-21 cm2/s xanthene derivative). Surface concentration was estimated to be 1.55x10-13 mol cm-2 flourene derivative and 2.00x10-13 mol cm-2. These compounds were used for the inclusion of parvalbumin antibodies immobilised onto clathrate platform by incubation and were evaluated as immunosensors for fish species identification. The antibody/antigen binding event was evaluated using UV/Vis spectroscopy, electrochemical impedance spectroscopy (EIS) and atomic force microscopy (AFM). The immunosensor response to parvalbumin in real samples of snoek (an indigenous fish species), tuna, fish paste, eyeshadow, lipstick, omega 3&6 and Scott's emulsion was evaluated. The sensitivity as calculated from EIS for each immunosensor was found to be 5.36x104 flourene derivative immunosensor and 4,11x104 xanthene derivative immunosensor and the detection limit of 1.50 pg/ml flourene derivative immunosensor and 2.42 pg/ml xanthene derivative immunosensor. The antibody/antigen binding was monitored as decrease in charge transfer resistance and increase in capacitance by EIS. The interfacial kinetics of the immunosensors were modelled as equivalent electrical circuit based on EIS data. The UV/Vis spectroscopy was used to confirm the binding of the antibody/antigen in solution by monitoring the intensity of the absorption peak.